Rheotaxis Response Based on Sexual Dimorphism in the Green Swordtail Fish, Xiphophorus hellerii - Muhammad Irsyad Abiyusfi Ghafari; Vita Fitrianti (Universitas Islam Negeri Mataram, 2020)
Morphological distinctions between males and females of a species are referred to by sexual dimorphism. It may result from various selection pressures affecting either sex or both and may occur in any dioecious species, including Green Swordtail fish, which are sexually reproductive. This study examined the different rheotaxis responses of Xiphophorus hellerii based on different sexes and morphological features. We analyzed ten adult males, ten gravid females, and ten non-gravid females of Xiphophorus helleri collected down the river and transferred into the column. We counted the number of the individual that performed positive rheotaxis (+), negative rheotaxis (-), and indifference response (0). The result showed different rheotaxis responses shown by male, non-gravid female, and gravid female X. hellerii. The highest percentage of positive rheotaxis response (movement against the current) was shown by non-gravid female X. hellerii, reaching up to 89%. Morphological differences between male, non-gravid female, and gravid female X. hellerii appear to affect the orientation and ability of X. hellerii in giving response against current and certainly has an impact on their survival in nature.